Renal Disease in Cystic Fibrosis: A Study at a Tertiary Care Center in Saudi Arabia (Bangladesh Journal of Medical Science, 2026)
Background Cystic fibrosis (CF) is a multisystem autosomal recessive disorder with increasing life expectancy, leading to the emergence of non-pulmonary complications, including renal involvement. Although renal disease has been reported in approximately 5.1% of CF patients globally, evidence from Arab populations remains scarce. Materials and Methods A retrospective observational study with an embedded case series was conducted at a tertiary care center in Saudi Arabia. Medical records of 430 patients diagnosed with CF between 1984 and 2018 were reviewed. Clinical and laboratory data were collected across four follow-up time points, from initial presentation to the most recent clinic visit. The primary outcomes assessed included the presence and types of renal complications, such as electrolyte disturbances, acute kidney injury, and chronic kidney disease. Results Out of 430 CF patients, three cases of renal disease were identified. All affected patients exhibited proteinuria, hematuria, and characteristic ultrasound findings, including increased renal echogenicity and loss of corticomedullary differentiation. Electrolyte abnormalities were also observed in all cases. Additionally, these patients demonstrated pulmonary involvement, including bronchiectasis and interstitial lung changes. A shared CFTR mutation (c.1418delG, exon 11) was identified in at least one allele in all three patients. Conclusion Renal involvement, although uncommon, represents a clinically relevant complication in patients with CF. Early and routine renal monitoring is essential for timely detection and management, which may help prevent progression to chronic kidney disease and reduce the need for renal replacement therapies.Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S244-S251